Assessment of physical activity of Universiti Putra Malaysia staff using a pedometer - Soh, Kim Geok; Soh, Kim Lam; Husain, Ruby; Omar Fauzee, Mohd Sofian; Yusof, Aminuddin; Tan, Huey Yee; Japar, Salimah (Africa Association for Health, Physical Education, Recreation, Sport and Dance, 2009)
The association between a sedentary lifestyle and susceptibility to diseases and poor physical and mental health are well established. This research sought to assess the level of physical activity undertaken by Universiti Putra Malaysia (UPM) staff as well as ascertain the factors influencing their physical activity participation. Two-hundred and twenty staff (113 females and 107 males) volunteered to participate in the study. In order to assess their physical activity level, the Yamex- Digi pedometer was attached to the participants daily for six consecutive days. The pedometer indicated that the average number of steps taken were 7,177 ± 2,518 a day. They ranked in the ‘low active’ category according to Tudor-Locke and Bassett (2004). A minimum of 10,000 steps a day, required for an ‘active’ lifestyle is needed to confer health benefits. It was concluded that the UPM staff were not benefiting much from their low level of physical activity. The major factor responsible for their low level of physical activity was found to be their lack of self motivation.